Using Small-Area Estimation to Describe County-Level Disparities in Mammography - Schneider, Karen L (Centers for Disease Control and Prevention, 2009)
INTRODUCTION: Breast cancer control efforts could benefit from estimating mammography prevalence at the substate level because studies have primarily analyzed health survey data at the national and state levels. The purpose of this study was to evaluate the extent to which geographic disparities exist in mammography use across counties in the contiguous United States. METHODS: We estimated county-level prevalence of recent mammography (past 2 years) for women aged 40 to 79 years by using synthetic regression, a small-area estimation method. The 2000 Behavioral Risk Factor Surveillance System (BRFSS), 2000 Census, Area Resource File, and Food and Drug Administration mammography facility data were merged by BRFSS respondents' county of residence. We conducted separate analyses to produce county-level prevalence estimates for each race and age group. RESULTS: Mammography use varied geographically, and the magnitude of geographic disparities differed by race and age. Nonwhite women showed the lowest prevalence of mammography and widest range in county-level estimates. Women aged 40 to 49 had generally lower prevalence than other age groups, while women aged 65 to 79 showed the greatest variation in county-level mammography estimates. CONCLUSIONS: Small-area estimation using BRFSS data is advantageous for surveillance of mammography use at the county level. This method allows documentation of geographic disparities and improves our understanding of the spatial distribution of mammography prevalence. Future interventions should consider this county-level geographic variation, targeting women in the neediest counties.